OPTIMALISASI KOMPETENSI GURU SEJARAH: SOSIALISASI SEJARAH BANDAR-BANDAR MAJAPAHIT DI KOTA DAN KABUPATEN MOJOKERTO - Deny Yudo Wahyudi; Slamet Sujud Purnawan Jati; Daya Negri Wijaya; Shela Dwi Utari; Vita Sabrina Azda Laili; Labuda Shofiya Ananda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Teachers must possess and apply a new set of skills and competencies in the 21st century that are emphasised by the transformative demands of modern education. This aims to prepare students for the various challenges of life in the future. Teacher competence in Indonesia is recognised as a key driver for improving the quality of education however, there are challenges in ensuring that all teachers have the necessary competencies. This is also required by history teachers, where history is indispensable for students as a foundation for acting in the present and future. To achieve this, teachers need to have competencies such as critical thinking, creativity, collaboration, digital literacy, and the use of technology. This study aims to improve the competence of Mojokerto City and District History MGMP teachers in the field of local history material and making infographic learning media. This research had four stages: problem identification, solution formulation/planning, socialisation, and evaluation. The findings of this study indicate an increase in competence after the implementation of service activities. The data showed a striking increase in the pre-test and post-test results, specifically by 9.49. This finding shows that the teachers can effectively understand local history and develop digital-based learning resources. This improvement suggests that the skills and expertise of educators can be effectively enhanced through socialisation. This article concludes that a collaborative digital learning environment has a positive impact on teachers' professional development. In addition, the results show that ongoing collaboration and support among educators can result in continuous growth in terms of knowledge and skills. This highlights the importance of creating opportunities for teachers to engage in collaborative learning experiences.